2022
DOI: 10.1002/cbdv.202200015
|View full text |Cite
|
Sign up to set email alerts
|

Design and Synthesis of Novel Dual Cholinesterase Inhibitors: In Vitro Inhibition Studies Supported with Molecular Docking

Abstract: The major cholinesterase enzymes, acetylcholinesterase (AChE) and butyrylcholinesterase (BChE), are important in the therapy of Alzheimer's disease (AD) based on the cholinergic hypothesis. As a result, in recent years, the investigation of dual cholinesterase inhibition methods has become important among scientists. In this study, novel N‐(4‐chlorobenzyl)‐3,4‐dimethoxy‐N‐(m‐substituted)benzamide derivatives were synthesized. Then, inhibitory properties of these derivatives were examined in human AChE and BuCh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 51 publications
(93 reference statements)
0
6
0
Order By: Relevance
“…Then Lineweaver–Burk graphs were drawn and K i constants were calculated (Figure 2). 32 While Tacrine (TAC) was used as standart inhibitor of cholinesterases, acetazolamide (AZA) was used as standard inhibitor of hCA isozymes 33,34 …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Then Lineweaver–Burk graphs were drawn and K i constants were calculated (Figure 2). 32 While Tacrine (TAC) was used as standart inhibitor of cholinesterases, acetazolamide (AZA) was used as standard inhibitor of hCA isozymes 33,34 …”
Section: Methodsmentioning
confidence: 99%
“…32 While Tacrine (TAC) was used as standart inhibitor of cholinesterases, acetazolamide (AZA) was used as standard inhibitor of hCA isozymes. 33,34…”
Section: In Vitro Inhibition Studiesmentioning
confidence: 99%
“…Therefore, increasing ACh stability towards catalyzed hydrolysis is the major approach to treating AD. [4][5][6][7][8][9][10] However, recent research has discovered a decreasing pH in the aging brain and Alzheimer's disease, [11] in which the enzyme becomes less active. [12] It implies that nonenzymatic hydrolysis potentially contributes to ACh depletion.…”
Section: Introductionmentioning
confidence: 99%
“…The enzyme is commonly believed to be the depletion's main origin. Therefore, increasing ACh stability towards catalyzed hydrolysis is the major approach to treating AD [4–10] . However, recent research has discovered a decreasing pH in the aging brain and Alzheimer's disease, [11] in which the enzyme becomes less active [12] .…”
Section: Introductionmentioning
confidence: 99%
“…For example, Karunakaran et al (13) studied human AChE-inhibitory activity of Convolvulus pluricaulis (an herb) in zebrafish with scopolamine-induced cognitive dysfunction and result showed that the inhibitor was bound to His447 of the catalytic triad, anionic subsite, and peripheral anionic site. Koca et al (14) synthesized a benzamide derivative to investigate potency against cholinesterases with predicted inhibition profiles of the derivative. Furthermore, Makarian (11) analyzed the most potent derivatives of donepezil using molecular docking analysis and results showed different moieties of the new compound binding to all the subsites of the binding site.…”
Section: Introductionmentioning
confidence: 99%